Image Processing in Cryo-Electron Microscopy of Single Particles: The Power of Combining Methods - Sorzano, Carlos Oscar S; Jiménez-Moreno, Amaya; Maluenda, David; Ramírez-Aportela, Erney; Martínez, Marta; Cuervo, Ana; Melero, Robert; Conesa, Jose Javier; Sánchez-García, Ruben; Strelak, David; Filipovic, Jiri; Fernández-Giménez, Estrella; et al. (Methods in molecular biology, 2021)
Cryo-electron microscopy has established as a mature structural biology technique to elucidate the three-dimensional structure of biological macromolecules. The Coulomb potential of the sample is imaged by an electron beam, and fast semi-conductor detectors produce movies of the sample under study. These movies have to be further processed by a whole pipeline of image-processing algorithms that produce the final structure of the macromolecule. In this chapter, we illustrate this whole processing pipeline putting in value the strength of "meta algorithms," which are the combination of several algorithms, each one with different mathematical rationale, in order to distinguish correctly from incorrectly estimated parameters. We show how this strategy leads to superior performance of the whole pipeline as well as more confident assessments about the reconstructed structures. The "meta algorithms" strategy is common to many fields and, in particular, it has provided excellent results in bioinformatics. We illustrate this combination using the workflow engine, Scipion.
Keywords: průběh práce; Molecular Biology; zobrazení jednotlivé molekuly; zobrazování trojrozměrné; Algorithms; Single Molecule Imaging; Workflow; Cryoelectron Microscopy; počítačové zpracování obrazu; Image Processing, Computer-Assisted; Macromolecular Substances; makromolekulární látky; elektronová kryomikroskopie; Imaging, Three-Dimensional; algoritmy; Computational Biology; molekulární biologie; výpočetní biologie